Design management apllied to value creation in the furniture industry (DAPesquisa, 2021)
With the advancement and more accessible values of technology, companies are trying to find new ways to maintain their position in the market. In this context, design management plays an important role in creating value for industries. The purpose of this study is to demonstrate, through a bibliographic review and a case study of the Ikea company, how design management allows the creation of competitive and innovative models in the industry. This research has an exploratory, descriptive, qualitative nature, bibliographic and systematic review of articles and graduate studies. As a result, it was possible to identify that the company Ikea created an innovative model called Democratic Design, developed from design management. This model provides a creative differential to the company, keeping it competitive in the furniture market. The study also shows that the most valued companies in the financial market use design management as a strategic tool in their institutions.
Keywords: Design, Industrial; Product management; Furniture industry and trade; Product differentiation; Designers